Acute Kidney Injury After Transcatheter Aortic Valve Implantation: Incidence, Risk Factors and Impact on Mortality - Martins, Ana (2020)
Introduction: Acute kidney injury is a frequent complication after transcatheter aortic valve implantation with great impact on morbidity and mortality. It is important to identify modifiable risk factors in order to develop preventive strategies. The aim of the study is to determine acute kidney injury incidence, risk factors and impact in patients that underwent transcatheter aortic valve implantation.Material and Methods: Retrospective study in 149 consecutive patients that underwent transcatheter aortic valve implantation at Santa Marta Hospital. The data was collected from the periprocedural records and stratified by the occurrence of acute kidney injury according to the AKIN classification.Results: A total of 149 patients, 43.0% male with median age 82.00 [77.50 – 85.00] years were included in the study. Incidence of acute kidney injury was 14.8% (n = 22). Female patients (OR 0.138, CI 95%; 0.022 – 0.854; p = 0.033) had a higher risk of that complication. Patients with acute kidney injury had longer hospitalizations (OR 1.043, CI 95%; 1.001 – 1.085; p = 0.043); acute kidney injury was associated with increased 30 day mortality (OR 13.889, 95% CI; 2.371 – 81.363; p = 0.004).Discussion: Acute kidney injury is associated with preprocedural variables and is a determinant of morbimortality. However, the retrospective character and the reduced sample size didn’t allow the determination of the precise weight of each factor.Conclusion: Acute kidney injury is a complication after transcatheter aortic valve implantation which played a significant role in morbimortality justifying its prevention.